REALISASI KESANTUNAN BERBAHASA MELALUI POLA KALIMAT DALAM WAWANCARA RESMI - Nurhasanah, Ima; Laksman-Huntley, Myrna (Universitas Hasanuddin, 2025)
This study examines the realization of politeness in the questioning patterns used by a Kompas TV journalist when interviewing the Managing Director of the IMF during the 2022 G20 Summit. The analysis focuses on three aspects: Leech’s (1993) politeness principles, sentence structure based on Kolln and Funk (2008), and the spontaneity of questions determined by the tendency to use written scripts. This study employs a qualitative method using data from an English-language interview transcript. The results show that non-spontaneous questions generally employ complex structures and polite modal expressions, while spontaneous questions tend to be more concise, using simpler structures yet still maintaining politeness through neutral and non-confrontational wording. These three aspects complement each other in maintaining the interviewee’s image and reducing potential face-threatening acts, particularly in sensitive diplomatic interactions. The findings emphasize that sentence structure and delivery play a significant role in shaping politeness within media discourse.